Getai kitsch : reinterpretation of Getai's aesthetics as a visual language for contemporary culture - Tan, Syivester (Nanyang Technological University, 2020)
While years of modernisation has allowed for rapid progression of Singapore and her citizens, it has in turn led to the decline of Chinese culture. Millennials today are far less likely to be involved in events relating to Chinese culture and heritage, such as Getai. No longer accustomed to this form of performance art, societal progression has caused millennials to think of Getai as non-progressive and distasteful; in other words, kitsch. This paper investigates the main factors contributing to the misconception of Getai, by delving into the formation and dilution of Chinese culture in Singapore, and how it contributes to the decline in appreciation of Getai. This paper also investigates the meaning of kitsch and why this term is being deployed to describe cultural products of Singapore. The final design deliverables consist of: A publication that documents, deconstructs and reinterprets Getai’s visual forms, allowing readers to appreciate Getai’s visual culture; applications of reinterpreted Getai visual forms on consumers’ products to showcase how Getai’s aesthetics can be brought into contemporary culture; and an open-source graphic library and typeface that encourages young Singaporeans to participate in bringing Getai’s visual culture into contemporary culture. This project aims to overcome the cultural estrangement younger Singaporeans feel towards Getai and cultivate appreciation towards it by encouraging efforts to reclaim its value in the contemporary world.